Belekhova L. I. Verbal poetic image in conceptual poetry (case study of American, Ukrainian and Russian poetry) - Belekhova L. I. (Philological Treatises, 2020)
The article focuses on defining the tendencies of postmodern poetic speech via analysis linguistic and extralinguistic factors of poetic images function in conceptual poetry as well as on revealing linguistic and cognitive mechanisms of the formation of a new type of images – parable.